2016
DOI: 10.1371/journal.pone.0168819
|View full text |Cite
|
Sign up to set email alerts
|

A High Level of Soluble CD40L Is Associated with P. aeruginosa Infection in Patients with Cystic Fibrosis

Abstract: ObjectiveThe aim of this study was to evaluate whether the concentration of sCD40L, a product of platelet activation, correlates with the presence of Pseudomonas aeruginosa in the airway of patients with cystic fibrosis (CF) and to determine its possible clinical association.MethodsSixty patients with CF, ranging in age from 2 months to 36 years, were studied. The demographics, cystic fibrosis transmembrane conductance regulator (CFTR) genotype, spirometry measurements, radiographic and tomographic scans, plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous studies showed that CD40L could bind to its receptors on macrophage surface and promote the secretion of inflammatory factors during infection, atherosclerosis, and myocardial infarction. 1921 In this study, the sCD40L level was significantly higher in UA patients than that of healthy control. This may be caused by platelet activation.…”
Section: Discussionmentioning
confidence: 46%
“…Previous studies showed that CD40L could bind to its receptors on macrophage surface and promote the secretion of inflammatory factors during infection, atherosclerosis, and myocardial infarction. 1921 In this study, the sCD40L level was significantly higher in UA patients than that of healthy control. This may be caused by platelet activation.…”
Section: Discussionmentioning
confidence: 46%
“…The normal range of sCD40L in the serum of healthy individuals is estimated to be 0.79 to 4.7 ng/mL [ 123 , 124 ]. Elevated levels of sCD40L have been found in several infectious diseases, including Pseudomonas aeruginosa infection in cystic fibrosis patients [ 125 ], visceral leishmaniasis caused by Leishmania infantum [ 126 ], meningococcal sepsis [ 127 ], DENV-2 [ 45 ], HIV [ 128 ], and periodontopathogens infections [ 129 ].…”
Section: Shedding Of Platelet Surface Proteins In Infectionmentioning
confidence: 99%